DETERMINATION OF THE FREQUENCY OF OCCURRENCE OF THE MOST IMMUNOGENIC ERYTHROCYTE ANTIGENS IN PATIENTS USING THE ACROSS OCTO-M AUTOMATIC ANALYZER - Владимир Вячеславович Павленко; Юлия Рамилевна Романова; Алиса Владимировна Матанцева; Ольга Борисовна Карелина; Евгения Александровна Каменева (Медицина в Кузбассе)
Studying the frequency of occurrence of the most immunogenic red blood cell antigens in patients is important for understanding immune reactions and ensuring effective methods of transfusion therapy. Specific immunogenic antigens contained in red blood cells can cause the formation of antibodies in recipients, which can lead to various hemolytic reactions and other complications. The need for careful screening of donor red blood cells and an individual approach to transfusion therapy will minimize the risk of immune complications and improve the safety of treatment.